Experimental research system evaluation of damage to national security in the sphere of state secrets - Дрейс, Юрій Олександрович (Ukrainian Information Security Research Journal, 2013)
State expert on secrets when classification of information to state secrets is conducted justification and determination of possible damage to national security if its disclosure or loss of material carriers of this information. Existing calculate the damage in most based on a conditional (scoring) estimates of predicted value. The paper presents the algorithm of functioning and experimental research developed evaluation system of damage to national security in the sphere of state secrets, which is based on a model of integrated presentation parameters damage, existing means of this sphere and the method of analysis and estimation of possible damage to both conventional (ball) units and in value (monetary) value of loss. The system uses an integrated database containing basic parameters and performance means of the procedure to ensure classification of information to state secrets and has the capability automated reporting the results of the evaluation.